Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1111/aos.13549
|View full text |Cite
|
Sign up to set email alerts
|

Increased frequency of retinopathy of prematurity over the last decade and significant regional differences

Abstract: The Swedish national ROP register revealed an increased incidence of ROP during an 8-year period and significant regional differences regarding the incidence of ROP and frequency of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
42
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 18 publications
7
42
1
Order By: Relevance
“…Fortunately, the meta-analyses did not show more blindness in spite of more severe ROP in the high saturation target group although some studies report increased blindness after new guidelines recommending higher target saturations were published. In a Swedish region, a significant 2.2-fold increase in treated ROP was found after changing recommendations to higher targets [29]. However, alarm limits were not tightly defined.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, the meta-analyses did not show more blindness in spite of more severe ROP in the high saturation target group although some studies report increased blindness after new guidelines recommending higher target saturations were published. In a Swedish region, a significant 2.2-fold increase in treated ROP was found after changing recommendations to higher targets [29]. However, alarm limits were not tightly defined.…”
Section: Discussionmentioning
confidence: 99%
“…A Cochrane review of all 5 trials, comprising nearly 5,000 infants, confirmed an increased risk of death at [18][19][20][21][22][23][24] [8]. It is likely that concerns about increasing the risk of ROP is one reason why not all NICUs have adopted higher SpO 2 targets [21][22][23]. However, our survey suggests that whilst many NICUs did change to higher SpO 2 targets, some with initial upper limits > 95% changed to an upper limit of ≤95%, most notably in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…CP is a condition that occurs globally, with a similar ratio among both developed and undeveloped countries. However, the etiology differs according to the socioeconomic status of the countries [5]. Congenital hemiplegia is the most common form of CP among children born at term and second to diplegia among children born prematurely [6].…”
Section: Introductionmentioning
confidence: 99%